A Case Study on the Influence of Friction Coefficient and Rotational Speed on Transient Thermoelastic Response of FGM Rotating Cylinder - Reza Koohi Faegh Dehkourdi; Mostafa Omidi Bidgoli; Mohammad Hosseini (Mechanics of Advanced Composite Structures)
The effect of friction and rotational speed parameters changes on the transient thermoelastic response of a rotating functionally graded cylinder with a short length subjected to thermal and mechanical loads are studied based on the First order shear deformation theory (FSDT). It is assumed that the cylinder is located on a friction bed and is rotating due to an external torque. The material property is assumed to be variable along radius according to a volume fraction distribution. Because temperature changes are unstable the changes in parameters are applied when the cylinder has reached a steady state. In the following, radial, longitudinal and angular displacement diagrams, as well as effective stresses due to changes in coefficient of friction and rotational velocities for longitudinal and radial directions, are drawn. The results show that these changes have significant effects on the measured parameters and in many industrial applications, these coefficients are not constant during the work period and have changed.